Sulphurization of Kapok (Ceiba Pentandra ) Seed Oil via H2S Bubbling Under UV Radiation and The Product’s Performance as Extreme Pressure Additives for Lubricant - Sukirno Sukirno; Cleo; Devan (ASEAN Journal of Chemical Engineering, 2024)
In this research, extreme pressure additive (EP additive) for lubricants was manufactured from Ceiba pentandra seed oil (kapok oil) via sulfurization reaction at a low temperature (50°C) by using a photochemical reactor under UV-radiation (254 nm). The sulfurization process was conducted by recirculating bubbling H2S gas through kapok oil filled in a glass chamber. The sulfurization reaction has been proven successful, as shown from the FTIR spectrum of the sulfurized kapok oil, where carbon-sulfur bond (C-S) vibration appears at a peak of 581 cm-1. It was also found that within 20 hours, the recirculated-bubbling sulfurization produced sulfurized kapok oil with a sulfur content of 32,682 ppm, viscosity of 72.17 cSt, and density of 0.92 g/cm3.  The product was then used as an EP additive by mixing it with mineral oil and testing it using a 4-ball wear tester.  The mineral oil containing sulfurized kapok oil 10% v/v or equal to sulfur content 3,268 ppm reduced wear amount by 98%. Results of corrosion tests via copper strip corrosion ASTM D130 showed that the copper strip’s color only had level 1a, meaning that mineral oil containing 10% Kapok oil as EP additives is not corrosive.